Roles of High-resolution Manometry in Predicting Incomplete Bolus Transit in Patients With Dysphagia. Issue 9 (October 2018) - Shi, Zhaohong; Guo, Jie; Clarke, John; Jin, Haifeng; Wang, Xinjun; Zhang, Nina; Stein, Ellen; Dhalla, Sameer; Pasricha, Pankaj J.; Chen, Jiande D.Z.
Abstract : Background: High-resolution manometry (HRM) is used to assess esophageal motility diseases. Abnormalities in a number of HRM parameters have been reported in patients with dysphagia. However, it is unclear whether some of abnormal HRM parameters are predictive of dysphagia. The aim of this retrospective study was to investigate the roles of HRM parameters in predicting incomplete bolus clearance (IBC) in patients with dysphagia using high-resolution impedance manometry. Methods: A total of 644 wet swallows were reviewed and analyzed in 63 patients with symptoms of dysphagia or reflux who underwent a clinical high-resolution impedance manometry test. IBC was defined based on impedance measurement. The relationship of each of abnormal HRM parameters with IBC was analyzed and their roles in predicting IBC were determined. Results: Patients with symptoms of both dysphagia and reflux showed the highest IBC rate, and patients with symptoms of reflux had the lowest IBC rate. The IBC was more prevalent in the distal esophagus. Premature contractions and peristalsis with large breaks were associated with a higher IBC rate in the proximal esophagus ( P <0.05); large breaks, ineffective peristalsis, and abnormalities of the esophageal gastric junction functions were associate with higher IBC rates in the distal esophagus ( P <0.05). Abnormalities in a number of motility parameters were able to predict IBC with high specificities and/or high sensitivity, such as pan esophageal pressurization, ineffective peristalsis, and large breaks. Abnormal integrative relaxation pressure of the lower esophageal sphincter with concurrent pan esophageal pressurization, ineffective peristalsis, or large breaks is predictive of IBC with nearly 100% of specificity. Conclusions: Abnormalities in a number of HRM parameters are not only useful in diagnosing esophageal motility diseases, but also valuable in predicting IBC during swallowing.